Performance Evaluation of Selected Ceramic Companies of Bangladesh - Masum, Abdullah Al; Johora, Fatema-Tuz- (Asian Business Review, 2012)
This paper applies performance evaluation of ceramic industry of Bangladesh and to test its financial soundness. The main aim is achieved through ratio analysis of four selected ceramic (Fu Wang, Monno, Shinepukur and Standard) companies in Bangladesh. Measurement of financial performance by ratio analysis helps identify organizational strengths and weaknesses by detecting financial anomalies and focusing attention on issues of organizational importance. The financial performance of this industry is measured in terms of profitability, solvency, efficiency and liquidity analysis and to test the financial soundness, Multivariate Discriminate Analysis (MDA) is used, which was developed by Prof. Altman. The study covers four public sector ceramic companies listed on Dhaka Stock Exchange. The study has been undertaken for the period of five years from 2006-7 to 2010-2011 and the necessary data has been obtained from the audited annual report of the selected companies. The liquidity position was very weak in all the cases of the selected companies and thereby reflecting the difficulties in paying short-term obligation on due date. Financial stability of the selected companies has shown an upward trend. This study will help investors to identify the nature of financial performance of the ceramic industry of Bangladesh and will also help to take investment decision.